Analisis Bermain Dengan Teman Sebaya Dalam Meningkatkan Perilaku Prososial Anak Usia Dini - Lutfiah Permata Lukman Hasibuan; Juli Maini Sitepu (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2022)
This study aims to determine the activities of playing with peers in improving the prosocial behavior of early childhood. This research includes quantitative research, using the correlational method. The research location chosen is Siti Hajar Islamic Kindergarten Medan, which is located on Jl. Jamin Ginting KM 11 Paya Bunder, North Sumatra. The population and sample in the study were all parents of group B students who found 44 parents. The data collection technique used is a questionnaire or questionnaire. While the data analysis used is a correlation test and a simple linear regression test. The results of the study obtained a correlation value or r = 0.692 in the strong category. And the simple linear regression test value obtained a significance value or p = 0 0.05. So Ho is rejected, meaning that there is an influence of playing with peers on the prosocial behavior of early childhood. So it can be said that playing with peers can improve prosocial behavior of early childhood in Siti Hajar Islamic Kindergarten. The large influence of playing with peers in increasing prosocial behavior of early childhood obtained a determination test value of 0.478 or 47.8% while the remaining 52.2% was contributed by other variables not explained in this study.